Sagittal Alignment May Not Correlate with Range of Motion in Ankle Arthritis and TAR - Ricardo Villar MD; Kira Lu; Jaeyoung Kim MD; Joseph Nguyen MPH; Jensen Henry MD; Constantine Demetracopoulos MD (Foot & Ankle Orthopaedics)
Submission Type: Ankle Arthritis Research Type: Level 3 - Retrospective cohort study, Case-control study, Meta-analysis of Level 3 studies Introduction/Purpose: Improving range of motion (ROM) is one of the most challenging objectives in total ankle replacement (TAR). While preserving motion is one of the advantages of TAR in comparison to ankle fusion, factors that interfere with ROM are not well established in the literature. Movement in the ankle joint predominantly occurs in the sagittal plane, yet no study has analyzed how sagittal alignment interferes with ROM. Our study aims to evaluate associations between preoperative and postoperative ROM and Sagittal Tibiotalar Alignment for TAR. We hypothesized that sagittal alignment parameters would correlate with ankle ROM. Methods: This study is a single-institution retrospective review of prospectively collected data from primary TARs from March 2019 – April 2022 with preoperative and postoperative weight-bearing radiographs. Ankle and global range of motion measurements were performed using previously validated methods. Sagittal alignment was evaluated by 2 observers using 3 methods: the sagittal tibiotalar ratio (TT ratio) pre and postoperatively, the anteroposterior offset ratio, and the tibial implant sagittal slope on the postoperative radiograph. 61 ankles were included for analysis (31 Wright Infinity, 21 Exactech Vantage and 9 Wright Inbone II). Correlation between changes in sagittal alignment and ROM measurements was addressed by Pearson’s correlation test (PCC). A PCC of 0.4 to 0.7 was considered moderate, while a PCC greater than 0.7 was strong and lesser than 0.4 was considered a weak correlation. Interclass correlation coefficients (ICC) and 95% confidence intervals were used to address interobserver reliability for the sagittal radiograph measurements. Results: Pre-operatively, the median TT ratio was 36.5 ± 7.5, while post-operatively it was 35.9 ± 6.3. The average tibial implant sagittal slope angle was 88.5° ± 2°. We found no moderate or strong correlation between any of the sagittal measurements and ROM. A statistically significant (p < 0.05) negative weak correlation was found between the sagittal pre op TT ratio and the pre op plantarflexion offset and global plantarflexion offset, indicating that an anterior translated talus may be associated with more plantarflexion preoperatively. Similarly, a weak negative correlation was found between the offset ratio and the post op dorsiflexion offset and post op total ROM, suggesting that an anterior translated talar implant may interfere with post op ROM, especially in dorsiflexion. Conclusion: Although restoring alignment is crucial in TAR, our study suggest a weak or no correlation between sagittal alignment and ROM in fixed bearing implants. Several facts could have influenced our findings. Variables that were not controlled, such as etiology. The literature is scarce in terms of ankle sagittal alignment, so we need a better understanding of what is abnormal. Our cohort was limited in terms of variations in sagittal alignment: TT ratio pre and post were very similar, tibial sagittal implant slope varied little and 33 patients had neutral AP offset. Further studies should take this into consideration.